Driving factors to competitive sustainability of SMEs in the tourism sector: An introspective analysis - John Amoah; Sulemana Bankuoru Egala; Solomon Keelson; Emmanuel Bruce; Raymond Dziwornu; Frank Agyemang Duah (Cogent Business & Management)
The services sector continues to play a major role in the transformation of economies. For instance, the tourism sub-sector, which is a key segment of the service sector has become one of the major contributors to economic transformation in developing economies. Given this prospect, stern competition has been created among tourism firms across the globe. However, the tourism sectors in most developing countries continue to grapple with competitive pressure challenging their competitive sustainability. Drawing on the theory of change, the purpose of this paper is to investigate factors that drive the competitive sustainability of small and medium enterprises in the tourism sector in Ghana. Data was collected from 310 SMEs in the tourism sector through the administration of a structured questionnaire and analyzed using Partial Least Square Structural Equation Modelling. The results show that price sensitivity, site maintenance, and entrepreneurial competency have a positive and significant effect on the competitive sustainability of small and medium enterprises in the tourism sector. By implications, the paper provides managers of tourism facilities with an encompassing mechanism aimed at improving tourism sites, enhancing the entrepreneurial competencies of staff, and adopting pricing strategies to enhance the competitive sustainability of the tourism sector from a developing country’s perspective. The study advances theories on tourism competitive sustainability.